The Effects of Pyrethroid Insecticide Resistance Development on the Behaviour of Malaria Vectors and their Impact on Malaria Transmission in Western Kenya - Gesuge, Machani, Maxwell (JOOUST, 2022)
Despite significant reductions in malaria transmission through the scaling up of vector control tools across sub-Sahara Africa since 2000, progress is stalling. This is partly attributed to the emergence of insecticide resistance and behavioral adaptations in malaria vectors. Whilst insecticide resistance has been widely investigated, the effect of specific insecticides on the rate of the emergence of insecticide resistance or the rate at which mosquitoes lose their insecticide resistance properties remains largely uncharacterized. There is sparse knowledge on the behavioral adaptations of resistant malaria vectors in response to the use of the current indoor intervention, despite their potential impact on malaria transmission. The study first, sought to understand the process of insecticide resistance development (phenotypic, genotypic, and metabolic changes), or resistance decay in the presence or absence of selection pressure, in Anopheles gambiae sensu stricto mosquitoes. Secondly, the study investigated the host-seeking behavior of resistant and susceptible phenotypes of Anopheles gambiae s.s in the presence of insecticides in the malariasphere and lastly, determined the effects of insecticide resistance on the resting behavior of malaria vectors and how it contributes to residual malaria transmission in western Kenya. To achieve the above aims, deltamethrin selected and unselected colonies of Anopheles gambiae were established in the presence and absence of insecticide pressure. The selection was done by exposing female mosquitoes to a standard diagnostic dosage of deltamethrin using the World Health Organization (WHO) tube bioassay test. The established colonies were color-marked with fluorescent powder and released inside semi-field structure to determine how the rise and change in insecticide resistance has affected whether mosquitoes feed inside or outside the house, and rest outdoors following intensified Long-lasting insecticide-treated nets (LLIN) usage. Laboratory based experimental research and cross-sectional study designs were used in this study. The indoor and outdoor resting mosquitoes were collected from highland and lowland sites in western Kenya to determine the effects of insecticide resistance on the resting behavior of malaria vectors and its impact on residual malaria transmission. The indoor collection was done using pyrethrum spray catches (PSC) and Mechanical aspiration (Prokopack). The outdoor collection was done using clay pots, pit shelter and mechanical aspiration. Polymerase Chain Reaction (PCR)-based molecular diagnostics was used for mosquito speciation, genotyping for resistance markers and to determine specific host blood meal origins. Enzyme-linked immunosorbent Assay (ELISA) was used to determine mosquito sporozoite infections. Microplate assay was performed to measure the three enzymatic activities (Monooxygenase, Esterase and Glutathione S-transferase) linked to insecticide detoxification. WHO criteria was used to classify tested mosquito populations as either resistant or susceptible. The frequency of the resistance allele was calculated using the Hardy Weinberg equilibrium test for kdr genotypes. Analysis of variance (ANOVA) was used to compare malaria vector density between indoor and outdoor locations. A generalized linear model (GLM) with binomial distribution and logit link function was used to compare the behaviors of resistant and susceptible mosquitoes between treatments. The mortality of the parent populations averaged iv 42% (ranging from 38% to 48%). Phenotypic resistance increased steadily in the selected strain (Mortality declined from 42-29%). The unselected strain progressively became more susceptible to deltamethrin over time (Mortality range; 42-97%). These two lines of mosquito populations differed significantly in monooxygenase and beta-esterase activities, but not in Voltage-gated sodium channel (Vgsc) gene mutation frequency, suggesting that metabolic detoxification mechanism plays a major role in generating moderate to high intensity of insecticide resistance. The proportion of selected resistant colony caught in the treated bed net trap was higher 43% (95% CI= [40.6-45.3]) compared to the unselected susceptible colony 28.3%. The number of unselected susceptible mosquitoes caught in the untreated bed net trap was higher 51.3% (95% CI= [48.8- 53.6]) compared to a treated bed net trap 28.3% (95% CI= [26.3-30.5]) (OR=2.65; P< 0.0001, An. funestus; F1, 655 = 36.555, p < 0.0001). The mortality rate for indoor and outdoor resting An. gambiae s.l F1 progeny was 37% vs 67%) respectively in Bungoma. In Kisian, the mortality rate was 67% vs 76%) respectively. The mortality rate for F1 progeny of An. funestus resting indoors in Bungoma was 32%. The overall sporozoite rate for indoor resting mosquitoes was 9% (An.gambiae s.s 8%, An. arabiensis 4% and An funestus 11%) and 4% ( An. gambiae s.s 5% and An. arabiensis 3%) for outdoors in Bungoma. In Kisian, the sporozoite rate was 1% for indoor resting An. gambiae. The higher indoor resting densities with increased insecticide resistance compared to outdoor resting vectors and reduced avoidance behavior of the selected resistant mosquitoes in the presence of insecticides underline the difficulties of controlling malaria vectors using the current interventions. This calls for supplemental vector control tools and the implementation of sustainable insecticide resistance management strategies in western Kenya. The rate of resistance decay to become fully susceptible from moderate-intensity resistance took 15 generations, supporting at least 1.5-2 years interval is needed when the rotational use of insecticides with different modes of action is considered for resistance management.
Keywords: Anthropophily; Behavioral resistance